ANALISIS SEMIOTIK DALAM PUISI “AKU INGIN” KARYA SAPARDI DJOKO DAMONO - Dera Rae Nursiami Harfi (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2020)
Poetry is a literary work in conveying messages through writing. Poetry can also be interpreted as an expression of one's soul in reading a poem. Poetry has rhythm, rhyme, arrangement of sounds and a myriad of beautiful meanings in each verse. But every verse of poetry contains signs that the reader does not understand, the signs contained in the poetry have implied meanings that must be clearly expressed so that the meaning of the poem is conveyed by the author. The purpose of this research is to describe each verse containing the semiotic sign in Sapardi Djoko Damono's poem “Aku Ingin”. In this study, researchers discussed semiotics. Semiotics is the science that studies signs, both markers and markers contained in each line of poetry so that the poetry produces an implied meaning. This study uses a qualitative descriptive method, which aims to describe, explain, and analyze the problems obtained in a study. Based on the results of this study, there is an element of sign or meaning contained in the poem "Aku Ingin" to convey someone's love sincerely and sacrifice so that it can be concluded that love the person you love sincerely and prove that love by sacrifice, not with words because love does not. can be measured in words but by the sacrifices made.